PKA distributions: Contributions from transmutation products and from radioactive decay. (December 2016) - Gilbert, M.R.; Sublet, J.-Ch.
Highlights: Primary knock-on atom (PKA) spectra under fusion neutron irradiation. PKA spectra for transmuted tungsten show variation with irradiation time. Daughter recoils of nuclear reactions can be as important as scattering PKAs. Recoils from radioactive decay in Fe, Al, and W are computed. In light elements decay recoils can contribute non-negligibly to PKAs. Abstract: The neutrons generated in fusion plasmas interact with materials via nuclear reactions. The resulting transmutations and atomic displacements have life-limiting consequences for fusion reactor components. A detailed understanding of the production, evolution and material consequences of the damage created by cascades of atomic displacements requires, as a vital primary input, a complete description of the energy-spectrum of initial (prompt) atomic displacement events (the primary knock on atoms or PKAs) produced by direct neutron nuclear interactions. There is also the possibility that the radionuclides produced under transmutation will create further PKAs as they decay, and so the rate of these must also be quantified. This paper presents the latest results from the analysis of PKA spectra under neutron irradiation, focussing particularly on the variation in PKA distributions due to changes in composition under transmutation, but also on the PKA contributions from radioactive decay of materials that become activated under irradiation.